20. ASSESSING THE RELATIONSHIP BETWEEN STRESS LEVEL, SLEEP QUALITY, LIFE QUALITY AND CHANGES IN FSH, LH, PROLACTIN HORMONE CONCENTRATIONS WITH THE RESULTS OF TREATMENT OF SEVERE ACNE VULGARIS WITH ISOTRETINOIN (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the relationship between stress level, sleep quality, quality of life and changes in FSH, LH, prolactin hormone levels with the results of treatment of severe acne vulgaris in female patients with isotretinoin. Research subjects and methods: Clinical trial, prospective, comparing results before and after 3 months of severe acne vulgaris treatment on 45 female patients with isotretinoin 20 mg/day at the National Dermatology Hospital from October 2022 to September 2023. Results: After 3 months of treatment, DASS21 score decreased from 13±12 to 11±12, P
Keywords: Acne, hormones, isotretinoin, quality of life, quality of sleep, stress.